The restoration feasibility of degraded Carex Tussock in soda-salinization area in arid region. (March 2019) - Wang, Xuehong; Zhang, Dongjie; Qi, Qing; Tong, Shouzheng; An, Yu; Lu, Xianguo; Liu, Yan
Highlights: It is not feasible to restore Carex Tussock when soda-salinization or second-salinization occurred. It is doable to establish Carex Tussock in undisturbed soil with suitable water conditions. Carex Tussock protection is more important than restoration. More attention should be paid to prevent salinization or second-salinization in arid and semi-arid area. Abstract: In the arid and semi-arid areas, Carex Tussock had deteriorated and disappeared as a result of water deficit and salinization due to human activities and climate changes. A green house experiment was carried out to testify the restoration feasible of Carex Tussock in salinization area. We used a factorial design with two soil conditions (degraded soil occurred salinization and undisturbed soil), two Carex Tussocks (degraded ones resulted from soda-salinization and well ones) and three water levels (long-term drought, seasonal inundation and long-term inundation). In soda-saline soil, degraded Carex Tussock subjected to long-term drought died finally, and could not be revived even the stress was eliminated. Degraded Carex Tussock subjected to the other two water treatments and well Carex Tussock in all water condition went dormant status until environment was improved. However, in the undisturbed soil, except for degraded Carex Tussock under the long-term drought, others successfully survived to the end of experiments, and the degraded ones could be revived when water condition was improved. In undisturbed soil, height, leaf width, leaf area, chlorophyll content and biomass (fresh biomass and dry biomass) of well ones were better than degraded ones. Above results illustrated that it was not feasible to restore Carex Tussock in the soda-saline soils no matter by water condition improvement or well Carex Tussock transplanted. However, transplanting degraded or well Carex Tussock to undisturbed soil could establish successfully. Besides, natural Carex Tussock protection should be paid more attention to avoid soil salinization or secondary salinization. Once salinization or secondary salinization extensively occurred, the degeneration of Carex Tussock would be irreversible.